The Impact of Knowledge Management on Cognitive Achievement in Sports Science: A Case Study in Boxing Education - Al-Hamdani, Fuad Abdul Mahdi Mahmoud; Abbas , Rawaa Abdul Ameer; Ghadhban, Saba Qays (Retos, 2025)
Introduction: Knowledge management plays a crucial role in students’ ability to acquire, organize, retrieve, and apply information, impacting academic performance. In sports sciences, especially in combat sports like boxing, effective knowledge management supports both theoretical understanding and practical skill application. Despite exposure to boxing through training and media, students’ academic performance remains inconsistent. Objective: This study examines the relationship between knowledge management and cognitive achievement among second-year students in the College of Physical Education and Sport Sciences at the University of Basrah. It evaluates how students manage knowledge and its impact on their retention and application of boxing-related concepts. Methodology: The study utilized the Knowledge Management Scale (KMS) and Cognitive Achievement Scale (CAS) to assess knowledge management and academic performance. Statistical analysis, including correlation, was used to assess the relationship between these variables. A sample of 120 students participated in the study. Results: A significant positive correlation (r = 0.564, p < 0.01) was found between knowledge management and cognitive achievement. Most students (42.1%) demonstrated average levels of both knowledge management and academic performance, indicating a need for improved knowledge management techniques. Discussion: The study highlights the importance of integrating structured knowledge management strategies, such as mental mapping and digital tools, into sports education to enhance cognitive and practical skills. Conclusion: Enhancing knowledge management strategies in boxing education can bridge the gap between theoretical knowledge and practical application, improving both cognitive and skill-based performance in sports sciences.